Pengaruh Substitusi Tepung Ubi Jalar Ungu Terhadap Karakteristik Fisik Roti Kukus Dengan Sourdough Dari Air Rendaman Apel - Rini Rahayu Sihmawati; Wardah; Ayu Anggraini Cahya Pitaloka (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2025)
This study aimed to determine the effect of flour substitution levels on the moisture content, expansion, and texture of steamed bread. The treatments consisted of five formulations: F0 (0%), F1 (10%), F2 (20%), F3 (30%), and F4 (40%) flour substitution. Data were analyzed using the Least Significant Difference (LSD) test at a 5% significance level to evaluate the effect of treatments on each physical parameter. The results showed that increasing the level of flour substitution had a significant effect on all tested parameters. The highest moisture content was observed in F4 (40%) at 39.22%, while the lowest was in F1 (10%) at 36.53%. Texture softness decreased as the substitution level increased, with the highest value in F0 (167.44 mm/100g/10s) and the lowest in F4 (88.52 mm/100g/10s). The expansion of steamed bread also tended to decrease, from 8.40% in F0 to 7.53% in F4. These results indicate that higher flour substitution levels reduce the dough’s ability to expand and form an elastic crumb structure due to decreased gluten content. Overall, the best formulation was obtained in treatments F1 (10%) to F2 (20%), as they produced steamed bread with balanced moisture, soft texture, and optimal expansion.   Keywords: steamed bread, flour substitution, moisture content, expansion, texture